An Error Tolerated Congestion Control Algorithm Based on Packet Loss Rate Measurement in Deep Space Communication Network - Junrong Yan; Yulong Lu; Peng Pan (Dianxin kexue)
Congestion control algorithms of TCP protocol previously used in space communications are mostly based on TCP Vegas algorithm.They always require accurately measurement of RTT,but it's very difficult to achieve in deep space communication networks which have very long and variable delay channel characteristics.An errors tolerated congestion control algorithm is proposed based on packet loss rate measurement.The algorithm sends data in the form of data blocks and gives an errors tolerated degree based on the history data.It measures the congestion state based on the current packet loss rate measurement,so it can achieve a smaller overhead and higher transmission efficiency.In addition,the usage of mathematical modeling methods simplifies the networks and simulates the real network traffic.The mentioned algorithm is compared with the classical congestion control algorithm.Analysis and simulation prove that thethroughput of improved algorithm is 34 percent better than Tahoe and 22 percent better than Reno,so it gets a better performance.